Particle size effects on the structure and emission of Eu3+:LaPO4 and EuPO4 phosphors - Gavrilović, Tamara; Periša, Jovana; Papan, Jelena; Vuković, Katarina; Smits, Krisjanis; Jovanović, Dragana J.; Dramićanin, Miroslav D. (Elsevier B.V., 2018)
This paper provides the detailed study of (nano)particle's size effect on structural and luminescent properties of LaPO4:Eu3+ synthesized by four different methods: high temperature solid-state, co-precipitation, reverse micelle and colloidal. These methods delivered monoclinic monazite-phase submicron particles (> 100 nm), 4 × 20 nm nanorods and 5 nm spheres (depending on the annealing temperature), 2 × 15 nm nanorods, and ultra-small spheres (2 nm), respectively. The analysis of emission intensity dependence on Eu3+ concentration showed that quenching concentration increases with a decrease of the particle size. The critical distance for energy transfer between Eu3+ ions is found to be 18.2 Å, and the dipole-dipole interaction is the dominant mechanism responsible for the concentration quenching of emission. With the increase in Eu3+ concentration, the unit-cell parameter slightly increases to accommodate larger Eu3+ ions at sites of smaller La3+ ions. Photoluminescent emission spectra presented four characteristic bands in the red spectral region: at 592 nm (5D0→7F1), at 612 nm (5D0→7F2), at 652 nm (5D0→7F3) and at 684 nm (5D0→7F4), while in small colloidal nanoparticles additional emission bands from host defects appear at shorter wavelengths. Intensities of f-f electronic transitions change with particles size due to small changes in symmetry around europium sites, while emission bandwidths increase with the reduction of particle size due to increased structural disorder. Judd-Ofelt analysis showed that internal quantum yield of Eu3+ emission is strongly influenced by particle's morphology.
The authors acknowledge the ﬁnancial support of the Ministry of Education, Science and Technological Development of the Republic of Serbia (Projects nos. 45020 and 172056). T.G acknowledges to the ERDF PostDoc project No. 1.1.1.2/VIAA/1/16/215 (1.1.1.2/16/I/001).
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Eu3+-doped LaPO4; Solid state synthesis; Co-precipitation; Reverse micelle; Colloids